Transcending Disaster Education: A Developmental Approach Ensuring Sustainability - Quazi, Afshan Naz (SCHOOL SCIENCE, 2017)
Our earth, with the present population estimate of 7.5 billion humans, has been a cradle to the evolution, transformation and manifestations of many civilizations that ever existed on its surface. The time elapsed and the human society proliferated with the development of science and technology through the modern thoughts brought about by three gigantic revolutions made in agriculture, industrial and information technology sectors of income and human sustainability. The continuance of human life on earth is intricately intertwined with the sustainability of the earth on micro to macro scale. The sustainability of earth bears the imprints of all those catastrophes that affect its ability to guard human life on it. The world with vast continental landmasses and having diversified topographic structures is bound to face multiplicity of natural hazards on local to regional scale. Natural events of such adverse effects on human property and life have led us to conceptualise these as disasters. The trend analysis of last 100 years over the earth reveal the fact that much have been changed by natural disasters with an average occurrence of 7 in 1914 to 341 disasters in 2014 per continent on a global scale. The present study focuses on how frequent the disasters have continued to harm our environment and up to what extent threatened existence of mankind in the last ten decades. The available data on past natural calamities have been studied to gauge the intensity and effects of these hazards and realising a better way to mitigate them by educating all for disasters and disaster management as this will ensure timely disaster preparedness in general. Each disaster occurs at the backdrop of some science in it. This necessitates natural disasters as a probable area of concern which awaits intrinsic study and investigations with enough scientific aptitude and enquiry in science education of our country. Natural disasters though a comprehensive theme to work upon is still a phenomenon least understood in our education system. The origins of such events of unforeseen calamities are originating and set in one country but its effects howsoever mild or severe it may be are widespread across national boundaries. To understand, mitigate and finally to manage them lies with the scientific community at our disposal. Without realising scientific spirit and integrating science behind disasters by each one of us, the goal to manage our earth resource and to prove a nature worthy of being called as sustainable, and hence notion of all round sustainable development remains devoid of reality.